Adsorption of ferric ions on the surface of bastnaesite and its significance in flotation. (1st November 2020) - Zhu, Xinyu; Lin, Yiming; Huang, Yang; Zhu, Yangge; Shi, Changxing; Wang, Weiqing
Graphical abstract: Highlights: Ferric ions have inhibitory effect on flotation of bastnaesite. Ferric ions are adsorbed with RE ions on bastnaesite surface. The interaction between ferric ions and RE ions through bidentate adsorption. The interaction mechanism between bastnaesite, ferric ions and H205 was studied. Abstract: In the system of 3-hydroxy-2-naphthyl hydroxamic acid (H205) collector, the adsorption of ferric ions on the surface of bastnaesite and its significance in flotation was investigated by micro-flotation tests, zeta potential measurements, adsorption experiments, solution chemistry analysis, X-ray photoelectron spectroscopy (XPS) measurements and density functional theory (DFT) calculations. From the results of our experiments, it can be known that ferric ions species (Fe(OH)3(s) ) can absorb on the surface of bastnaesite by interacting with RE(OH)x 3−x (x = 1, 2) (RE = Ce, La and Nd) to form RE-O-Fe-OH. And in this process, Fe(OH)3(s) is bound to RE(OH)x 3−x (x = 1, 2) mainly by bidentate adsorption. By bidentate adsorption with RE(OH)x 3−x (x = 1, 2), the addition of ferric ions decreases adsorption sites for H205, impedes the adsorption of H205 on the surface of bastnaesite, and then depresses bastnaesite flotation.